2015
DOI: 10.1093/acprof:oso/9780198724469.001.0001
|View full text |Cite
|
Sign up to set email alerts
|

Aliens and Strangers?

Abstract: In this work of qualitative sociology, Anna Strhan offers an in-depth study of the everyday lives of members of a conservative evangelical Anglican church in London. ‘St John’s’ is a vibrant church, with a congregation of young and middle-aged members, one in which the life of the mind is important, and faith is both a comfort and a struggle—a way of questioning the order of things within society and for themselves. The congregants of St John’s see themselves as increasingly countercultural, moving against the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…However, this critical discursive focus can also risk reproducing a decontextualized, dehistoricized account of Jewish identity and practice. Significantly, this can mirror a similarly reified account of the 'Protestant' framing of religion-as-belief and conversely of nonreligion as non-belief (Lee 2015;Strhan 2015). To put this simply, my ethnography shows that, unsurprisingly, the terminology of the 'secular', '(un) belief' and related words do have purchase within the self-descriptions of British Jews, including for myself as a Jewish ethnographer shaped within an assimilatory secular-Protestant culture.…”
Section: Interrogating 'Unbelief': Jewish Genealogical Interventionsmentioning
confidence: 86%
“…However, this critical discursive focus can also risk reproducing a decontextualized, dehistoricized account of Jewish identity and practice. Significantly, this can mirror a similarly reified account of the 'Protestant' framing of religion-as-belief and conversely of nonreligion as non-belief (Lee 2015;Strhan 2015). To put this simply, my ethnography shows that, unsurprisingly, the terminology of the 'secular', '(un) belief' and related words do have purchase within the self-descriptions of British Jews, including for myself as a Jewish ethnographer shaped within an assimilatory secular-Protestant culture.…”
Section: Interrogating 'Unbelief': Jewish Genealogical Interventionsmentioning
confidence: 86%
“…In relation to the particular religious context in this study, English evangelical Christianity, sociologists of religion have observed the predominantly middle-class contexts in which key evangelical networks have developed historically (Guest 2007: 27) and the middle-class status of many of its leaders and flagship churches has been highlighted (Guest 2007;Strhan 2012Strhan , 2015. Recent ethnographic study (Strhan 2012(Strhan , 2015 of a conservative evangelical congregation in London examines the embodied nature of evangelical subjectivity and pays attention to how this is shaped by its metropolitan, urban location, including the classed nature of this context.…”
Section: Class and Religious Identitiesmentioning
confidence: 99%
“…Recent ethnographic study (Strhan 2012(Strhan , 2015 of a conservative evangelical congregation in London examines the embodied nature of evangelical subjectivity and pays attention to how this is shaped by its metropolitan, urban location, including the classed nature of this context. However, overall, despite highlighting the classed nature of English evangelicalism, research on evangelical subjectivity has often primarily focused on the impact of gender and ethnicity with more limited attention to class (see for example Aune 2006;Baillie 2002;Hunt and Lightly 2001;Schaefer 2004;Toulis 1997).…”
Section: Class and Religious Identitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…3.11 Riverside's work with children and young people today suggests alternative aspirations. While many evangelicals’ engagements with young people are still today shaped by a conversionist logic, and many focus primarily on middle-class children, there are also growing efforts across different evangelical constituencies to engage in different forms of ‘mission’, shaped by a consciousness of the exclusions perpetuated by evangelical culture's dominant white middle-class culture (Elisha 2011; Strhan 2013, 2015). Open evangelicals self-consciously distinguish their urban engagements from historical and other contemporary evangelicals’ desires for the religious conversion of non-Christians.…”
Section: Ragged Schools and Riverside's Educational Ambitionsmentioning
confidence: 99%